Critical Role of LMCD1 in Promoting Profibrotic Characteristics of Lung Myofibroblasts in Experimental and Scleroderma‐Associated Lung Fibrosis - Bogatkevich, Galina S.; Atanelishvili, Ilia; Bogatkevich, Andrew M.; Silver, Richard M. (Arthritis & rheumatology (Hoboken, N.J.), 2023)
Objective Interstitial lung disease (ILD) is a serious complication and leading cause of mortality in patients with systemic sclerosis (SSc). In this study, we explored the role of LIM and cysteine‐rich domains protein 1 (LMCD1) as a novel factor in the pathogenesis of SSc‐related ILD (SSc‐ILD). Methods The expression and effects of LMCD1 were studied in lung tissue samples and fibroblasts from SSc‐ILD patients and control subjects as well as in lung tissue samples from animal models. Results LMCD1 was consistently elevated in lung tissue samples and in fibroblasts isolated from SSc‐ILD patients as compared to controls. Additionally, LMCD1 was found to be highly expressed in the lung in the fibroblast‐specific protein (FSP)–driven, constitutively active transforming growth factor β receptor type I (TGFβR1) transgenic mouse model of ILD and the bleomycin‐induced mouse model of ILD. In lung fibroblasts from SSc‐ILD patients, LMCD1 is an essential factor for the TGFβ‐induced generation of type I collagen, fibronectin, and α‐smooth muscle actin (α‐SMA). Depletion of LMCD1 by small interfering RNA reduced the expression of extracellular matrix proteins and lowered transcriptional activity and expression of α‐SMA, as well as decreased the proliferation and contractile activity of SSc‐ILD lung fibroblasts. In dense fibrotic areas of affected lung tissue, lung LMCD1 colocalized with α‐SMA. In cultured scleroderma lung fibroblasts, LMCD1 colocalized and interacted with serum response factor which mediates LMCD1‐induced contractile activity of lung fibroblasts. Conclusion Our study identifies LMCD1 as a profibrotic molecule contributing to the activation of myofibroblasts and the persistent fibroproliferation observed in SSc‐ILD. Thus, LMCD1 may be a potential novel therapeutic target for patients with SSc‐ILD.